Composition analysis and formation pathway comparison of PM1 between two pollution episodes during February 2017 in Beijing, China. (15th February 2020) - Wang, Xiaoqi; Wei, Wei; Cheng, Shuiyuan; Lv, Zhe; Wang, Chuanda; Niu, Yuan
Abstract: SO4 2−, NO3 − and NH4 + (SNA) are the major components of particulate matter in Beijing. In this study, hourly concentrations of SNA in PM1 were measured through an Aerodyne Aerosol Chemical Speciation Monitor (ACSM) at an urban site of Beijing, from February 3rd to 20th of 2017. The analysis of the differences between two pollution cases during the sampling period was further conducted. The results showed that the concentrations of NO3 −, SO4 2− and NH4 + were 38.9 ± 10.5 μg/m 3, 41.9 ± 22.2 μg/m 3 and 31.3 ± 10.6 μg/m 3 respectively in the first case. A negative correlation was reflected between the PM2.5 concentrations and the following two ratios: 1) NO3 − /SO4 2− ; 2) [NH4 + ] to ([NO3 − ]+2[SO4 2− ]), with a correlation coefficient of −0.92 and −0.76 respectively. In the second case, the PM2.5 concentrations (proportions) were much higher, with values of 49.9 ± 17.0 μg/m 3 (22.9 ± 7.7%), 42.3 ± 15.8 μg/m 3 (20.3 ± 7.2%) and 33.1 ± 10.1 μg/m 3 (15.3 ± 4.3%). In contrast. The two ratios were positively correlated with the PM2.5 concentrations, along with the correlation coefficient of 0.77 and 0.62. Hence, it is palpable that two pollution cases were sulfate and nitrate dominant in respective. The emission characteristics due to the Chinese Spring Festival before P1 might be a major cause. A modeling-monitoring coupled approach was established for the recognition of the secondary conversion of SO4 2− and NO3 − . Results showed that sulfate/nitrate aged ratio (SAR and NAR) and sulphur oxidation ratio (SOR) in the second case were 0.48 ± 0.23, 0.22 ± 0.07 and 0.38 ± 0.23. They were all higher than those of the first case whose values were 0.32 ± 0.15, 0.18 ± 0.05 and 0.22 ± 0.12, which indicated that secondary conversion of precursors was enhanced in the second case. Although the OH concentrations were of no obvious difference in both cases, the average concentrations of H2 O2, NO2 and the relative humidity were much higher in the second case, which provided sufficient conditions and time for the formation of SO4 2− and NO3 − . Highlights: The concentration and proportion of SNA was much larger during pollution periods. Larger RH with higher H2 O2 and O3 concentration could promote sulfate formation. RH could be responsible for the enhanced secondary conversion degree of NOx. Surface and vertical wind field could lead to the accumulation of air pollutants.